2010
DOI: 10.1002/ejoc.201000377
|View full text |Cite
|
Sign up to set email alerts
|

Addition of Azomethine Ylides to Aldehydes: Mechanistic Dichotomy of Differentially Substituted α‐Imino Esters

Abstract: The formal 1,3-dipolar cycloaddition of azomethine ylides and aldehydes is explored, as hydrolysis of the resulting oxazolidine product gives facile access to valuable syn-β-aryl-β-hydroxy-α-amino esters. The use of using benzaldehydederived imines as the ylide precursor results in 1,3-dipolar cycloaddition with high conversions but low diastereoselec-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 69 publications
(73 reference statements)
0
13
0
Order By: Relevance
“…Thus, activation of aromatic aldehyde-derived α-iminoesters 117 by a Ag(I)/PPh 3 catalyst generated the N-metalated azomethine ylides 118, which underwent cycloadditions with benzaldehyde 2a to yield predominantly 4,5-trans oxazolidines 119 (Scheme 29, Table 15). Subsequent hydrolysis of the oxazolidine cycloadducts furnished the corresponding syn-β-aryl-β-hydroxy-α-amino esters [104]. Scheme 29.…”
Section: Scheme 28 Cycloaddition Of Azomethine Ylide 58 To 2-pyridalmentioning
confidence: 99%
“…Thus, activation of aromatic aldehyde-derived α-iminoesters 117 by a Ag(I)/PPh 3 catalyst generated the N-metalated azomethine ylides 118, which underwent cycloadditions with benzaldehyde 2a to yield predominantly 4,5-trans oxazolidines 119 (Scheme 29, Table 15). Subsequent hydrolysis of the oxazolidine cycloadducts furnished the corresponding syn-β-aryl-β-hydroxy-α-amino esters [104]. Scheme 29.…”
Section: Scheme 28 Cycloaddition Of Azomethine Ylide 58 To 2-pyridalmentioning
confidence: 99%
“…Initially, Cu salt decomposes diazo compounds to generate electrophilic Cu-carbenoid A, [1,10] which is then attacked by acetonitrile to produce nitrile ylide intermediate B or its enolate counterparts C. [8a,11] Amidine 4a may be obtained through either path I or path II. In path I, enolate C undergoes intramolecular [3+2] cycloaddition to produce oxazole D. [8a,11h] Then, oxazole D interacts with A to generate ylide E, [12] which can be intercepted by sulfonamide to furnish F. [8,11e] Next, intermediate F releases the Cu catalyst and affords G. Finally, intermediate G undergoes ring-opening [6,7] and 1,4-H shift to access the desired product 4a. On the other hand, intermediate B might be trapped by sulfonamide to furnish I, [8,11e] which then decomposes into J and regenerates the Cu catalyst (path II).…”
Section: Resultsmentioning
confidence: 99%
“…[5] In pioneering works, Vedejs has demonstrated that they are convenient azomethine ylide precursors in 1,3-dipolar cycloadditions with alkynes or alkenes (Scheme 1b). [6] In these reactions, [6,7] azomethine ylide was generated by ring-opening of oxazole through tandem alkylation and phenylsilane-induced reduction. To the best of our knowledge, the in situ generation of oxazole ylide and subsequent interception by nucleophile were underexplored up to now.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Somfai and co-workers used Vedejs' oxazole method to generate azomethine ylides for a reaction with aldehydes. [70] The corresponding oxazolidine 162, precursor ofhydroxy α-amino ester 163, was provided in 89 % yield with dr 2. 3 , no significant improvement to the yield or diastereoselectivity was observed.…”
Section: Azomethine Ylidesmentioning
confidence: 99%